Teaching unit on pets for English language learners - Zhang, Tianqi (Kansas State University, 2015)
Due to the fact that some English as a foreign language students lack motivation to learn English, this report will discuss how to promote their motivation by structuring appropriate lesson plans; giving students authentic L2 input; designing meaningful and communicative activities; choosing the right type of question to create learning opportunities; and using the guided inductive instructional approach for grammar teaching. Also, it will discuss how to prepare to be a 21st century teacher. The second part of this report contains detailed lesson plans for a unit on pets in which pedagogical theory is put into practice. This unit is mainly designed for low intermediate level English learners. The objectives of this lesson plan not only aim for improving students’ English language skills but also developing their animal and environmental protection awareness.
Keywords: Lesson plan; Pet unit; English; Pedagogy; Language learner; Instructional approaches; English as a Second Language (0441); Foreign Language Instruction (0444)